Electronic portfolios: Demonstrating student competence against external accreditation standards - Stanley, David; Glaister, Karen (Curtin University, 2012)
The aim of this eScholar project was to evaluate the effectiveness of an electronic portfolio as a learning and professional development resource for clinical-based health professionals; in the first instance its use by nursing students was explored. Portfolios have been used in nursing practice as a repository of evidence against nursing standards since the 1990s. Early portfolios were paper based, whilst recent iterations have evolved into electronic portfolio formats. An iPortfolio, available to all students studying at Curtin University, was integrated into the clinical practice units within the Bachelor of Science (Nursing) program as a suitable adjunct to support student learning and assessment. A cross-sectional study was conducted in 2010, involving a convenience sample of 115 students in the first semester of their course. A questionnaire solicited data on demographics, information technology skills, iPortfolio use, its structure and function and impact on the learning process. The information technology skills required for iPortfolio use were met by the majority of the study population, despite some having irregular access to computers and the Internet. Some onerous iPortfolio functionalities limited the full application of the tool for demonstrating professional-based competencies; however its value was recognised by users. Using the tool supported learning processes, particularly reflective practice, gaining feedback and self-determination of learning capacity. The results suggest the iPortfolio has potential as an electronic learning and assessment tool. With minimal modifications, its affordances support the demonstration of a skill set and evidence display against Curtin’s graduate attributes and the Australian Nursing and Midwifery Council’s competencies.